Ang batang natutong magpakumbaba (The child who learned to be humble) - Villanueva, Rene O.; Denso, Almar (Quezon City Lampara Publishing House, Inc., 2009)
"Va-va-boom is a shiny, fast, and elegant toy car. Many others admire him. But he is arrogant. he does not know how to beg one's pardon or ask for an apology. He also does not know how to use "po" and "opo." One time, he engages a train in a race. He dashes down the street without any concern for those he sideswipes or runs over. As a result, he bumps into a fence. Grandfather Uban tells the story of why lack of humility brings nothing good."
Ang aklat ng kagandahang asal = A book of values
Text in Filipino and English.
Keywords: Respect -- Fiction; Modesty